The Role of TDP-43 in SARS-CoV-2-Related Neurodegenerative Changes - Kim, Dong-Hwi; Kim, Jae-Hyeong; Jeon, Min-Tae; Kim, Kyu-Sung; Kim, Do-Geun; Choi, In-Soo (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The coronavirus disease 2019 (COVID-19) pandemic has been linked to long-term neurological effects with multifaceted complications of neurodegenerative diseases. Several studies have found that pathological changes in transactive response DNA-binding protein of 43 kDa (TDP-43) are involved in these cases. This review explores the causal interactions between severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and TDP-43 from multiple perspectives. Some viral proteins of SARS-CoV-2 have been shown to induce pathological changes in TDP-43 through its cleavage, aggregation, and mislocalization. SARS-CoV-2 infection can cause liquid-liquid phase separation and stress granule formation, which accelerate the condensation of TDP-43, resulting in host RNA metabolism disruption. TDP-43 has been proposed to interact with SARS-CoV-2 RNA, though its role in viral replication remains to be fully elucidated. This interaction potentially facilitates viral replication, while viral-induced oxidative stress and protease activity accelerate TDP-43 pathology. Evidence from both clinical and experimental studies indicates that SARS-CoV-2 infection may contribute to long-term neurological sequelae, including amyotrophic lateral sclerosis-like and frontotemporal dementia-like features, as well as increased phosphorylated TDP-43 deposition in the central nervous system. Biomarker studies further support the link between TDP-43 dysregulation and neurological complications of long-term effects of COVID-19 (long COVID). In this review, we presented a novel integrative framework of TDP-43 pathology, bridging a gap between SARS-CoV-2 infection and mechanisms of neurodegeneration. These findings underscore the need for further research to clarify the TDP-43-related neurodegeneration underlying SARS-CoV-2 infection and to develop therapeutic strategies aimed at mitigating long-term neurological effects in patients with long COVID.